2012
DOI: 10.1186/1742-2094-9-123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers of gold nanoparticle toxicity in rat brains

Abstract: BackgroundGold nanoparticles (AuNPs) are finding increased use in therapeutics and imaging. However, their toxic effects still remain to be elucidated. Therefore this study was undertaken to study the biochemical effects of AuNPs on rat brain and identify potential biomarkers of AuNP toxicity.MethodsMale Wister rats weighing 150–200 g were injected with 20 μg/kg body weight of 20-nm gold nanoparticles for 3 days through the intraperitoneal route. The rats were killed by carbon dioxide asphyxiation 24 h after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 26 publications
5
65
2
Order By: Relevance
“…Similar result was also observed in primary granule cells in vitro (Yin et al, 2013). Moreover, some other metal nanoparticles like gold nanoparticles may not release metal ions, but caused deleterious biological effects through the induction of oxidative stress (Siddiqi et al, 2012), which hinted the particle-specific effects. Preliminary data in our lab also showed high concentrations of gold nanoparticles did significantly decrease the viability of astrocytes (unpublished data).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar result was also observed in primary granule cells in vitro (Yin et al, 2013). Moreover, some other metal nanoparticles like gold nanoparticles may not release metal ions, but caused deleterious biological effects through the induction of oxidative stress (Siddiqi et al, 2012), which hinted the particle-specific effects. Preliminary data in our lab also showed high concentrations of gold nanoparticles did significantly decrease the viability of astrocytes (unpublished data).…”
Section: Discussionsupporting
confidence: 70%
“…ion content of AgNPs suspension could not fully explain the observed toxicity (Kawata et al, 2009) and the substantial toxicities caused by some other metal ion free nanoparticles like gold nanoparticles (Siddiqi et al, 2012) demonstrated the particle effects of metal nanomaterials. The argument on how much toxicity of AgNPs is related to the particle per se is continued and it is much of importance to clarify the differences in toxicities of AgNPs and its released ions.…”
mentioning
confidence: 99%
“…The cell may die by apoptosis, as in the case of moderate permeability transition pore opening and poly (ADP-ribose) polymerase activation with a preservation of cellular ATP, or by necrosis, as in the case of widespread permeability transition pore opening and poly(ADP-ribose) polymerase overactivation, which leads to massive nicotinamide adenine dinucleotide (NAD) consumption and the collapse of cellular ATP (Pacher et al 2007). Cardoso and colleagues (2014) suggested that the GNPs-induced DNA damage in the cerebral cortex of rats is related to oxidative stress and may lead to inflammation after administration, as it generates large amounts of ROS (Siddiqi et al 2012). Thus, we believe that the alteration found in the enzymes involved in energy metabolism in the organs of rats after administration of GNPs was related to oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
“…5A). Nanoparticles can induce enhanced lipid peroxidation and inflammatory reactions in rat brains, which could be a major toxicological paradigm for engineered nanoparticles [37,38]. Mitochondria are likely to be sensitive to nanoparticle cytotoxicity [39]; therefore, we further verified the subcellular high temperature requirement protein A2 (HtrA2) distribution following LNs or PEGylated LNs injection.…”
Section: Effect Of Lns Pegylation On Neurovascular Damagementioning
confidence: 97%